Effects of high temperature and shading on grain abscisic acid content and grain filling pattern in rice (Oryza sativa L.). (2nd October 2018) - Tsukaguchi, Tadashi; Tanaka, Ryuta; Inoue, Hironori; Nakagawa, Hiroshi
ABSTRACT: Abscisic acid (ABA) is a key factor regulating starch biosynthesis genes and is involved in assimilate partitioning to individual spikelets. The objective of this study was to clarify the effects of high temperature and shading during grain filling on grain ABA content and the grain filling pattern of spikelets located at different positions in a panicle. We grew the rice cultivar 'Koshihikari' in pots in 2009 under two temperature regimes and two light conditions during grain filling. We periodically measured grain dry weight and grain ABA content (pmol per grain) and concentration (pmol per grain dry weight). Shading increased a grain weight difference between superior and inferior spikelets while high temperature decreased the difference regardless of light condition. High temperature decreased ABA content and concentration in grains. There was a close correlation between mean grain ABA content and mean grain-filling rate averaged over the first half of grain filling.